Infective endocarditis: the specific features of its course, the criteria for diagnosis, differential diagnosis (part II) - B S Belov; G M Tarasova; B S Belov; G M Tarasova (Современная ревматология, 2008)
Infective endocarditis (IE) is today characterized by polyetiology due to a wide range of pathogens. The paper describes the specific features of the clinical picture of the disease in relation to the etiological agent, which have, in some cases, a crucial role in the choice of empiric antibiotic therapy. Significant clinical polymorphism, obscure symptoms, and monosyndromic onset as guises all enhance the importance of the differential diagnosis of IE, at its early stages in particular. Basic approaches to differentiating IE from the diseases in which differentially diagnostic problems arise to the utmost are outlined.